Triflic Acid Mediated Fries Rearrangement of 3-Dienyl-2-azetidinones: Facile Synthesis of 3-(But-2-enylidene)quinolin-4(3H)-ones - Anand, Amit; Mehra, Vishu; Kumar, Vipan (Synlett, 2013)
β-Lactam-synthon-interceded synthesis of 3-(but-2-enylidene)quinolin-4(3H)-ones has been described via triflic acid mediated Fries rearrangement of 3-butadienyl-2-azetidinones. The described protocol provides a direct access to C-3 functionalized quinolin-4(3H)-ones and does not suffer from the disadvantages associated with conventional routes.
Keywords: 3-dienyl-β-lactam; triflic acid; Fries rearrangement; quinolin-4(3H)-one; β-lactam synthon protocol